(Table 1) Sand, silt and clay at DSDP Leg 75 Holes - Gerald W Bode (PANGAEA, 1984)
The distribution of sand, silt, and clay was determined on 10-cm**3 sediment samples collected at the time the cores were split and described. The sediment classification used here is that of Shepard (1954), with the sand, silt, and clay boundaries based on the Westbrook (1922) scale. Thus, the sand, silt, and clay fractions are composed of particles whose diameters range, respectively, from 2000 to 62.5 μm, 62.5 to 3.91 μm, and less than 3.91 μm. This classification is applied regardless of sediment type and origin; therefore, the sediment names used in this table may differ from those used elsewhere in this volume, e.g., a slit composed of nannofossils in this table may be called a nannofossil ooze in a site summary chapter. Standard sieve and pipette methods were used to determine the grain-size distribution. The sediment sample was dried and dispersed in a Calgon solution. If a sediment sample failed to disaggregate, it was treated with a sonic probe and, if necessary, hydrogen peroxide. Sediment samples which resisted this treatment were not analyzed.
Supplement to: Bode, GW (1984): Appendix I. Grain-size analyses. In: Hay, WW; Sibuet, J-C; et al. (eds.), Initial Reports of the Deep Sea Drilling Project (U.S. Govt. Printing Office), 75, 1301-1303, https://doi.org/10.2973/dsdp.proc.75.app.1984